ИСПОЛЬЗОВАНИЕ РАДИОИЗОТОПОВ ДЛЯ РЕКОНСТРУКЦИИ СТАДИЙ РАЗВИТИЯ СОВРЕМЕННЫХ ОВРАГОВ - Беляев В.Р.; Голосов В.Н.; Сидорчук А.Ю.; Уоллбринк П.Д.; Мюррей Э.С. (My University, 2005)
Authors suggest new method of gully history reconstruction for the last 50 years, based on 137Cs and 210Pbex-dat-ing of proluvium. The application of this method to a certain gully investigation together with a traditional geologic -geomorphologic studies has allowed to determine the thickness of the gully deposits, to fulfill their detailed stratifi-cation, to reveal the main events of the gully development during the period under consideration. The comparison with the data on land-use and precipitation has helped to suggest possible causes of these events.
Keywords: 551.4.012:551.435.162